Pengaruh Disiplin Kerja, Lingkungan Kerja Dan Manajemen Pengetahuan Terhadap Kinerja Karyawan PT Supra Matra Abadi - Ramadhani, Rahmah; Halimatussa’diah (Universitas Negeri Medan, 2025)
The exploration examination intends to decide if work discipline somewhat significantlyaffects the exhibition of PT Supra Matra Abadi representatives. Accomplishes the workplace tosome extent affect the exhibition of PT Supra Matra Abadi representatives. Does information theboard to some extent affect the exhibition of PT Supra Matra Abadi workers. Take care of businessdiscipline, workplace and information the board at the same time affect the exhibition of PT SupraMatra Abadi representatives. The information investigation procedure utilized is the acquaintedquantitative examination strategy with the assistance of the SPSS program. This study utilizesdifferent direct relapse. The example in this study was 57 respondents. Essential informationassortment utilized a poll. The consequences of the review demonstrate that work disciplinesomewhat meaningfully affects the exhibition of PT Supra Matra Abadi representatives. Theworkplace to some extent affects the exhibition of PT Supra Matra Abadi representatives.Information the board to some extent meaningfully affects the presentation of PT Supra Matra Abadirepresentatives. Work discipline, workplace and information the executives all the whilemeaningfully affect the presentation of PT Supra Matra Abadi representatives.